Manajemen Sumber Daya Manusia Implementasi Dalam Pendidikan Islam - Kaswardi (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Human resource management is one of the areas of general management which includes terms of planning, organizing, implementation and control. Human resources are considered to be an increasingly important role in achieving the objectives, the various experiences and results of research in the field of human resources are gathered systematically in the so-called human resource management. Human resource utilization, is a process of leader activities that intend to employ employees who give enough achievements and do not employ employees who are not useful. Some efforts in improving human resources in Islamic Education: (a) improving the study of religious schools with public universities from basic to college, (b) Establishing coaching of learners Aga to be human Believers and fear Allah to God Yme, as well as religious education play an active role for the development of science and technology, and (c) Higher education religions develop scientific minds in order to understand and internalize and able to Translating religious teachings accordingly and in accordance with people's lives.